Lactoferrin Levels in the Gastric Tissue of Helicobacter pylori-Positive and -Negative Patients and Its Effect on Anemia - Yaşar Doğan; Tülay Erkan; Zerrin Önal; Merve Usta; Gülen Doğusoy; Fügen Çullu Çokuğraş; Tufan Kutlu (Mediators of Inflammation)
Aim. To determine gastric tissue lactoferrin (Lf) levels of Helicobacter pylori- (Hp-) positive and -negative patients and its effect on anemia. Methods. Cases in which initial presentation was of abdominal pain and that were Hp-positive at endoscopy were included. Hp-positive cases and -negative controls were divided into two groups. Results. The study included 64 cases (average: 10.2±0.4 years, 39 male and 25 female). Lf levels were subsequently studied on 61 cases. 45 (73.8%) of these were Hp-positive, while 16 (22.2%) were Hp-negative. In Hp-positive cases, mean staining percentages and density of glands in the antral mucosa were 45.5±4.7% and 1.9±0.1, respectively. Hp-negative cases showed significantly different values of 17.8±4.5% and 1.3±0.2, respectively. Hemoglobin and serum ferritin values of Hp-positive cases were 12.7±0.2g/dL and 32.5±2ng/mL, but these were comparable with Hp-negative cases (12.6±0.1g/dL and 30.7±4.4ng/mL). Conclusions. Tissue Lf was significantly higher in Hp-positive cases compared to Hp-negative cases, but no difference was observed between the two groups with regards to hemoglobin and ferritin level. As a result, it is difficult to say that this rise in Lf plays a role in the development of iron deficiency anemia in Hp-positive patients.